Elastohydrodynamic lubrication of point contact in oil starvation conditions at high mnperatures - Дмитриченко, Н. Ф.; Миланенко, A. A.; Мнацаканов, Р. Г.; Золотарева, Е. П.; Карпенко, Л. Ф. (Proceedings of National Aviation University (archive), 2000)
The processes of lubricant starvation are systematically analyzed in the point contact of friction ft high temperatures. The results show that the lubricant starvation condition and temperature Bgime of lubrication gives a new basis for the evolution and choice of lubricating materials for fearing using elastohydrodynamic criteria of durability